Effects of pond age and a commercial substrate (the water cleanser™) on natural productivity, bacterial abundance, nutrient concentrations, and growth and survival of MARRON (CHERAX CAINII Austin, 2002) in semi-intensive pond culture - Cole, A.; Tulsankar, S.; Saunders, Ben; Fotedar, Ravi (Elsevier BV, 2019)
© 2018 Elsevier B.V. The effects of a commercial substrate (The Water Cleanser™) (TWC1), and pond age, on bacterial abundance, nutrient concentrations, natural productivity and marron production, were investigated on a commercial marron (Cherax cainii) farm. The farm had 21 ponds, categorised as: 10 new ponds (2 juvenile, 4 grow-out, and 4 brooder; 5 with TWC, 5 without) and 11 old ponds (5 juvenile, 4 grow-out, and 2 brooder; 5 with TWC, 6 without). At the end of 7 months, TWC had no significant effects on the concentration of total ammonia nitrogen (TAN), nitrite nitrogen (NO2-N) and nitrate nitrogen (NO3-N), but reduced the concentration of orthophosphate. The initial concentrations of NO2-N, NO3-N after 18 weeks, and orthophosphate after 12 weeks, were significantly higher in old ponds. The phytoplankton abundance, after 6 weeks and 18 weeks, and bacterial abundance after 6 weeks were significantly higher in old ponds. Water quality and natural productivity in old and new ponds showed temporal fluctuations. There were no significant effects of TWC on phytoplankton or zooplankton abundance and diversity. In old ponds, there was a significant increase in juvenile marron final biomass of 26.3% with TWC, attributed to higher survival rate. The results suggest that TWC can be used to improve juvenile marron production.